If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -1x = -13 Solving 10 + -1x = -13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -1x = -13 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = -13 + -10 -1x = -13 + -10 Combine like terms: -13 + -10 = -23 -1x = -23 Divide each side by '-1'. x = 23 Simplifying x = 23
| X^2-x+17=0 | | X/2-(x-1/3)=1/9 | | -[10z-(14z+9)]=9+(3z+3) | | 6x-3=91 | | 40-3(2w+1)=11w-3(11+w) | | 3+x=117 | | x^3-2x^2+7x-14=0 | | 66/22r+(16/16-1)=r+(72/3/3) | | tanx=2sinx | | -1(3-4)+1x^2= | | 9s-5q=-4u | | n+9/3=44/9 | | 2+x=120 | | 2(7x+2)+12(x+1)=12 | | 25xsquared-20x+4=0 | | 4-4(1+-4x)=32 | | 5/6(2y+4)=10 | | 4n-10=5n-6 | | n+9/2=44/9 | | cos^2(x)=cosx | | 5-x=3x+9 | | 9-3x-1=6x+10 | | x/(x+3)=(x-4)/3 | | x^3/15 | | 8+(11/p)=10/p^2 | | 3y-y=-16 | | 4-4(1-4x)=32 | | 2x+2=314 | | 1-2n=n-14 | | 8+11/p=10/p^2 | | -4(-2)+3(4+2(-4))= | | 5t-3=33-t |